Effectuating Food Sovereignty without Violating the Rights of Indigenous People: A Case Study of the Merauke Integrated Food and Energy Estate Project - ., Sefriani; Thontowi, Jawahir; Wartini, Sri (KnE Social Sciences, 2023)
This study aimed to examine how the Merauke Integrated Food and Energy Estate (MIFEE) project negatively affected the human rights of the surrounding communities and what steps the government should undertake to achieve food sovereignty without infringing on the rights of the indigenous peoples involved in the initiative. This study employed a conceptual and historical approach and was analyzed qualitatively. The findings of this research indicated that the affected communities, particularly the Malind Anim tribe, experienced human rights violations, including those related to land rights; the right to work; the right to a reasonable standard of living; the right to a safe and healthy environment; the right to food and clothing since they were no longer able to meet and produce their own food needs, and infringement of the rights to culture; self-determination; and free, initiative, and informed consent; as well as the rights to freedom of expression; expression of opinion; and the right to gather. As a result of these violations, the ability of the environment to support life is lost, which has the potential to alight genocide. The suggested solution is to reinstate MIFEE’s original intent, implement moratoriums, evaluate the projects that negatively impacted indigenous peoples’ anthropology and ecology, and provide access to comprehensive forest conversion information. Affected communities are also encouraged to participate fully and effectively, and the granting of permits must consider the principle of justice. Keywords: Food sovereignty, human rights, Malind Anim